EMPOWERING WOMEN IN IMPROVING FAMILY WELFARE THROUGH CULTURED INDEPENDENT WOMEN CLASS PROGRAM - Pasaribu, Vera Asihna Riris; Manalu, Dimpos; Purba, Debora Betti; Waruwu, Putra Perdamaian (FISIP Universitas Malikussaleh, 2024)
Women's empowerment has become the main focus in efforts to improve family welfare. One of the approaches taken is a cultural independent class program which aims to develop the potential of women to preserve cultural identity in their area so that they can actively contribute to improving the quality of life and family income. The aim of this research is to determine women's empowerment in improving family welfare through a culturally independent women's class program. The method used in this research is qualitative and data is obtained by observation, documentation, interviews, documentation and focused discussions (FGD). The results obtained from this research are increasing family welfare and supporting national development goals as well as creating positive changes in society and increasing women's understanding of the importance of gender equality and cultural mainstreaming in achieving sustainable prosperity.keluarga. Salah satu pendekatan yang dilakukan adalah program kelas mandiri berbudaya yang bertujuan untuk mengembangkan potensi yang dimiliki oleh perempuan untuk melestarikan identitas budaya di daerahnya sehingga dapat berkontribusi aktif dalam meningkatkan kualitas hidup dan penghasilan keluarga. Tujuan penelitian ini untuk mengetahui pemberdayaan perempuan dalam meningkatkan kesejahteraan keluarga melalui program kelas perempuan mandiri berbudaya. Metode yang digunakan dalam penelitian ini adalah kualitatif dan perolehan datanya dengan observasi, dokumentasi, wawancara, dokumentasi dan diskusi terfokus (FGD). Hasil yang diperoleh dari penelitian ini adalah meningkatnya kesejahteraan keluarga dan ikut mendukung tujuan pembangunan nasional serta menciptakan perubahan positif terhadap masyarakat dan meningkatkan pemahaman perempuan tentang pentingnya kesetaraan gender dan pengarustamaan budaya dalam pencapaian kesejahteraan yang berkelanjutan.